Assessment of Knowledge and Consumption Patterns of Soybean, Moringa Oleifera, Aloe Vera and Other Agro-Resources: The Case of the Elderly and Pregnant/Nursing Women in Lome, Togo - Mensah, Tonyi R.; Eklou-Lawson, Mamy; Gbeasor-Komlanvi, Fifonsi A.; Ekouevi, Didier Koumavi; Karou, Damintoti S.; Ameyapoh, Yaovi; A. de Souza, Comlan (European Scientific Journal, ESJ, 2018)
Purpose: To assess how soybean products and other agro-resources are known and consumed by some vulnerable populations in Lome (Togo). Methods: A cross sectional study was conducted from March to April 2015 among people aged 50 years and over attending two Pension Fund departments and pregnant and nursing women attending Bè Hospital in Lome. Data were collected using a pre-tested face-to-face questionnaire. Participants were surveyed about their knowledge and consumption habits of soybean, Moringa oleifera, Aloe vera products and other agro-resources. Results: A total of 847 respondents were included in the study with 426 pregnant/nursing women and 421 people aged 50 years and over. The majority of respondents were married (39.5%) and 45.3% of the elderly people were widowed. At least nine over ten respondents (96%) knew soybean products and 76.8% of them reported a lifetime consumption of soybean products. The available and most consumed agro-resources included tofu (82.7%), moringa leaves (87.2%) and soy flour (29.7%). The least consumed products were soymilk, soy yogurt and moringa juice. Respondents also reported using moringa tea and soap, as well as Aloe vera juice and toothpaste. Conclusion: Soybean products and other agricultural resources are well known and consumed by people living in Lome. Data on actual food intake is useful to public health professionals and food safety risk assessors. It is important to inform the public at large of the recognized benefits of some foods that will provide solutions to their health problems.